4PL digital business models in sea freight logistics: The case of freighthub - Tim Gruchmann; Nadine Pratt; Jan Eiten; Ani Melkonyan (Logistics, 2020)
For years, the freight forwarding industry has been facing high levels of global competition. Accelerating this development, new and digital competitors are entering the market, striving to make freight logistics even faster, cheaper, and more predictable. Digitalization processes change traditional logistics businesses, leading to more efficient, flexible, and de-centrally organized logistics services. Sea freight operations, in particular, have the potential to better fulfill customer-specific requirements in competitive and complex environments by integrating digital technologies. Therefore, it is essential to understand how automating informational processes, such as freight brokering, affect business models in the logistics service industry. The present study qualitatively analyzed the case of FreightHub, a fourth-party logistics (4PL) sea freight agency, and compared its business model with traditional third-party logistics (3PL) business models. Applying a digital business model conceptualization, the present paper presents an extended framework for digital sea freight business models. In this line, the study contributes to theory and practice by refining business model research in the maritime transportation context, and providing managerial implications about the opportunities and threats of a digital transition in this industry.
Keywords: 650; digital business model; fourth-party logistics (4PL); sea freight logistics; third-party logistics (3PL)